Cyberbullying: Shaping the use of verbal aggression through normative moral beliefs and self-efficacy. (December 2018) - Veiga Simão, Ana Margarida Vieira da; Ferreira, Paula; Francisco, Sofia Mateus; Paulino, Paula; de Souza, Sidclay Bezerra
This study investigates the mediating effect of normative moral beliefs about cyberbullying behavior and self-efficacy beliefs to solve cyberbullying incidents in the relationship between adolescents' personal moral beliefs and the use of the content from verbal aggressions they witnessed in situations of cyberbullying. A total of 1607 students responded to an open-ended question regarding the content of verbal aggression they observed in cyberbullying situations, as well as questionnaires concerning personal and normative moral beliefs about cyberbullying behavior and self-efficacy beliefs to solve cyberbullying situations. Through content analysis, findings revealed nine distinct categories of content, which are in line with verbal aggression in cyberbullying behavior. Normative moral beliefs and self-efficacy beliefs mediated the relationship between adolescents' personal moral beliefs and using the content from verbal aggressions to communicate online. These results offer insights to develop authentic and interactive intervention programs that teach adolescents to communicate assertively, as a step toward preventing cyberbullying.